2018
DOI: 10.1016/j.dib.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Survey data on teaching strategies and product innovation: A focus on selected university students in Nigeria

Abstract: The main objective of this study was to examine the effectiveness of the teaching methods adopted in motivating university students’ in Nigeria to engage in product innovation. Emphasis was laid on Covenant University in Nigeria which is the pioneer institution to offer entrepreneurship education in Nigeria. The study adopted quantitative method with a descriptive research design to establish trends related to the objective of the study. Survey was be used as quantitative research method. The population of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…From Table 2, it showed that teaching strategies and curriculum content has an influence (R 2 ) of 82.5% on building graduates' employability. This finding is corroborated by the study in Olokundun et al (2018). The result of the findings helped to develop a framework for increasing building graduates' employability in Figure 2.…”
Section: Factors Influencing Building Graduates' Employabilitysupporting
confidence: 71%
“…From Table 2, it showed that teaching strategies and curriculum content has an influence (R 2 ) of 82.5% on building graduates' employability. This finding is corroborated by the study in Olokundun et al (2018). The result of the findings helped to develop a framework for increasing building graduates' employability in Figure 2.…”
Section: Factors Influencing Building Graduates' Employabilitysupporting
confidence: 71%
“…Por tanto, se necesitan nuevos enfoques y metodologías educativas que se centren en habilidades técnicas y multidisciplinares con base en las características, capacidades y necesidades de los estudiantes universitarios (Arrue y Zarandona, 2019;Romero y Garay, 2018). Una de las posibles soluciones a lo anterior, es la implementación de métodos de enseñanza que tengan un impacto significativo y positivo en la generación de innovación de productos por parte de los estudiantes (Olokundun et al, 2018). Por ello, las instituciones educativas han determinado la necesidad de incluir temas relacionados con la ciencia, tecnología e innovación con el objetivo de incentivar un pág.…”
Section: Innovación En La Universidadunclassified
“…Furthermore, Abolarinwa, et al [3] stated that the purpose of strategies is to assist a company in reaching a certain goal in terms of market development, size, tenure, improved productivity processes, aggregate sales and profitability. Jamai, et al [4] note that innovation includes both the progress of ma rket processes and their execution in addition to advances in goods and services [5]. The ability of the firm to identify and take advantage of strategies for market development paves the way for improvement and development [6].…”
Section: Introductionmentioning
confidence: 99%